Synthesis, biological evaluation and molecular modeling of a novel series of fused 1,2,3-triazoles as potential anti-coronavirus agents - Karypidou, Konstantina (2018)
Fil: Karypidou, Konstantina. Katholikie Universiteit Leuven; Bélgica.